Analyse des alternances codiques dans la production orale des futurs enseignants en classe de français langue étrangère (FLE) a l’école normale supérieure de Somanya au Ghana - Agbo, J.K. (My University, 2021)
This research focuses on code switching in the oral presentation of trainee teachers in French as a foreign language (FLE) class. The study seeks to examine how future teachers deploy code switching as an oral communication strategy during FLE. To draw on the intricacies of this phenomenon, this study adopts a mixed approach (quantitative and qualitative data analysis. The instruments used for data collection include questionnaire and audiovisual recording. The target population of our study includes 77 learners from the Mount Mary College of Education Somanya in Ghana. The results of the quantitative analysis serve as clues to comprehend and appreciate the intensification of the alternate use of the two languages (French and English) in oral presentation. Moreover, the articulation of the two approaches, macro and micro, allows us to highlight the functions of code alternation both in the epilinguistic discourse of the speakers than in their actual language practices. The study also shows that code switching is a way of speaking, which in our investigations contributes on the one hand to the development of the verbal repertoire in interaction and leads to code convergence. On the other hand, it fulfills several functions such as serving as a stylistic strategy and a resource for regulating turns during a speech event.
Research Article
Keywords: Code switching; oral presentation; choice of language; epilinguistic discourse; FLE